Power shift in the transformation and upgrading of the service sector—Empirical evidence from China - Xiaochen Geng (PLoS ONE, 2025)
In recent years, as the global economy has entered the “service economy” period, improving the service industry’s total factor productivity, realizing high-quality development, and better playing its supportive role in the real economy and its function of improving people’s well-being have become the top priorities for its development. The service industry is growing fast, yet its production and operations are putting pressure on the environment. For this reason, this paper incorporates environmental constraints into the analysis of the transformation and upgrading of the service industry to decompose and analyze the sources of green growth of the service industry. We find that: first, the level of green technology efficiency in the service industry is low, there is a downward trend, and the green technology efficiency gap widens significantly across provinces. Secondly, GTFP in the service sector is declining in general, with large inter-provincial differences, and the obstacle to growth lies in the deterioration of green technical efficiency, while the driving force for growth lies in green technological progress. Thirdly, labor productivity in the service sector has improved considerably, but all at the cost of high inputs, and the growth contribution of green total factor productivity and its constituent factors is negative, and the whole is still in the input factor-driven stage. Finally, the factors affecting GTFP in services are multifaceted, mainly involving structural, environmental regulatory, economic, social and institutional factors. This paper offers a theoretical foundation for further promoting the transformation and upgrading of the service industry to attract jade.